Analysis of The Influence of Nutritional Status Variables and Environmental Sanitation on The Event of Diarrhous to Children - Astiti, Feni; Zuraida, Reni; Bakri, Samsul; Berawi, Khairunnisa (Riviera Publishing, 2022)
Introduction: Diarrhea in 2019 became the second leading cause of death in children under five. The causes of diarrhoea include infection, malabsorption, and food and are influenced by several factors such as behavioural, nutritional, environmental, and socioeconomic factors. This study aimed to analyze the effect of variables on nutritional status and environmental sanitation on the incidence of diarrhoea in children under five in the South Lampung Regency. Method: This study is survey research with a cross-sectional design and uses binary logistic regression analysis. The samples taken were 380 toddlers aged 6-59 months. Result: 10 of the 21 predictor variables had a significant effect on the 5% significant level of the incidence of diarrhoea, where there were nine predictor variables, including poor/poor nutritional status, history of exclusive breastfeeding, clean water sources from BOR wells, clean water sources from PDAM. mountain spring drinking water sources, latrine facilities, septic tank facilities, managed waste management, and the floor of a ceramic house can reduce the incidence of diarrhea with odds ratio and [p=] values of 0.06[0.000], 0.33[0.017], 0.01[0.0000], 0.02[0.000], 0.02[0.004], 0.04[0.000], 0.01[0.025], 0.02[0.001], and 0.10[0.000]. Toddlers living in noncoastal areas have a 1.08 times higher chance of experiencing diarrhoea than coastal areas. In contrast, one variable, namely the age of toddlers, can increase the susceptibility to diarrhoea in toddlers with the odds ratio and [p=] values of 1.04 [0.007, respectively. Conclusion: This study shows that the influence of nutritional status variables and environmental sanitation has a great possibility to reduce the incidence of diarrhoea in children under five, namely in the group of nutritional status variables, including poor/poor nutritional status, age of toddlers, and history of exclusive breastfeeding.